Safari in South Africa - Lumry, Amanda; Hurwitz, Laura; McIntyre, Sarah (Bellevue, WA : Eaglemont Press, 2003)
Riley travels with his Uncle Max to check on the animal population at a South African game reserve.
Keywords: Game reserves -- Africa; Wildlife conservation; Animal ecology -- Africa